Migration and Remittances in CIS Countries during the Global Economic Crisis - Canagarajah, Sudharshan (World Bank, Washington, DC, 2012)
Despite the fact that the free flow of people across borders is the lynchpin of today's globalized world, more importance is usually given to the unrestricted movement of capital and goods. As a consequence, the effects of the financial crisis on the issue of migration have largely been ignored by the international community. The World Bank and other international organizations are examining ways to mitigate the effects of the financial crisis on migration and foster productive dialogue and partnerships among both sending and receiving countries, and the migrants themselves. This article describes the effects of the crisis in the Commonwealth of Independent States (CIS), proposes reforms to mitigate its effects, and suggests actions to encourage self-sustaining progress in the area of migration in the future.